PERLINDUNGAN HUKUM TERHADAP KONSUMEN OBAT TRADISIONAL BERBAHAN KIMIA OBAT DI INDONESIA - Meirin Azzahra, Laila; Salim, Irsyad Fadhlurrahman; Sari, Linda Purnama; Jakti, Hilal Kuncoro; Sugiartiningsih (Ganesha Civic Education Journal, 2026)
The circulation of traditional medicines containing Chemical Drug Substances (BKO) is a serious problem that has the potential to endanger public health and violate consumer rights. The addition of BKO to traditional medicines is done to provide a quick effect, but this practice is contrary to applicable legal provisions in Indonesia. This study aims to analyze the legal basis governing the circulation of traditional medicines containing BKO and the forms of legal protection for consumers. The research method used is a literature study with a qualitative approach, through a review of relevant regulations, books, and journal articles in the period 2016–2026. The results show that consumer protection has been expressly regulated in Law Number 17 of 2023 concerning Health, Presidential Regulation Number 49 of 2023, West Java Regional Regulation No. 3 of 2025, and various BPOM regulations. Legal protection is carried out through preventive efforts in the form of supervision and education, as well as repressive efforts in the form of administrative and criminal sanctions against business actors. However, the implementation of legal protection still faces obstacles, so that strengthened supervision and increased public legal awareness are needed.